Unveiling the Global Economic Impacts from Demographic Change in East Asia: An Estimation and Web Explores - Ardita, Andin; Marktanner, Marcus (Department of Development Economics, Universitas Sriwijaya, 2024)
This paper explores the economic consequences of demographic changes on development in 208 countries through 2100. We employ panel fixed effects models to estimate long-run equilibrium relationships between capital stock, labor force, and economic growth. Cointegration analysis confirms the existence of these long-run relationships. We affirm that there is a steady, long-run relationship between GDP, capital stock, and population. We also present our findings in an interactive web application, allowing users to explore how population shifts might impact economies worldwide. Highlighting key trends, we offer an illustrative case study of East Asia, while emphasizing the tool's universal applicability. Thus, this work does not seek to engage in specific academic discourse, but rather endeavors to contribute a valuable resource for informed public dialogue concerning the global economic implications of anticipated demographic transformations. The results show that the